Models of Student Care in the Digital Age: Perspectives of Imam Al-Ghazali and Burhanuddin Al-Zarnuji - Subaidi Subaidi; Muksin Muksin; Abd. Wahed; Ely Fitriani; Moh. Abdullah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2026)
Pesantren play an important role in shaping students’ moral character through an integrated system of spiritual, intellectual, and behavioral formation. However, modernization, digitalization, and shifting social values pose significant challenges to traditional models of nurturing and character education. This study aims to comparatively analyze the educational concepts of Imam al-Ghazali and Burhanuddin al-Zarnuji, particularly in relation to student nurturing and character formation, and to formulate an integrative conceptual framework applicable to contemporary pesantren education. This research employs a Systematic Literature Review (SLR) following the PRISMA protocol. Scholarly works published between 2013 and 2025 were collected from Scopus-indexed journals, Google Scholar, and other peer-reviewed databases. Inclusion criteria focused on studies discussing al-Ghazali’s and al-Zarnuji’s educational thought, Islamic pedagogy, and pesantren-based character education. After screening and eligibility assessment, selected articles were analyzed using thematic coding and comparative synthesis to identify convergences, distinctions, and potential conceptual integration between both scholars’ perspectives. The findings reveal that al-Ghazali emphasizes tazkiyat al-nafs, moral exemplarity, and spiritual purification as the core of education. In contrast, al-Zarnuji highlights sincere intention, disciplined learning, and the internalization of adab. While both prioritize character formation, they differ in pedagogical orientation, spiritual transformation versus practical ethical discipline. Their integration offers a holistic nurturing model that balances spiritual depth, intellectual rigor, and behavioral discipline. This model provides theoretical and practical implications for strengthening character education and sustaining pesantren resilience in the digital era.